New Zealand : Financial Sector Assessment Program: Technical Note-Regulation and Oversight of Financial Market Infrastructures. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note assesses regulation and oversight of financial market infrastructures (FMIs) in New Zealand. The regulatory and oversight framework for FMIs in New Zealand is undergoing a major reform. The Reserve Bank of New Zealand and the Financial Markets Authority (FMA) currently lack sufficient legal powers to identify and address risks building up in FMIs, partly because the regime is voluntary and the authorities do not have the appropriate toolkit to pursue their oversight objectives. It is recommended that supervisory practices be formalized and staff resources increased. The role of the FMA should be further clarified.